Accurate Reconstruction of Gas Turbine Blade Geometry Using 3D/2D Rigid-Registration and CT View Optimization - Hristo Valtchanov; Nicolas Piché; Vladimir Brailovski; Justin Byers; Catherine Desrosiers; François Guibault (e-Journal of Nondestructive Testing)
Complex parts created through casting or 3D printing processes often possess intricate internal cavities that serve performance-critical functions. Non-destructive X-ray or computed tomography (CT) testing plays a crucial role in the quality assurance process of turbine blades by allowing precise measurement of internal channels, ensuring adherence to the thermal and structural performance requirements. In our study, we utilize a gas turbine blade as a case study, highlighting the significance of its internal flow channels. These channels are essential for cooling the blade during operation, and the functional lifespan of a gas turbine blade is significantly influenced by the effectiveness of its interior cooling system. The dimensional accuracy of the interior cooling system is thereby crucial for maintaining the blades and, thus, the turbine’s service life.